Social Miasm Theory: Revisiting Chronic Illness from the Meta-Perspective of Suppression - Salazar, Stephinity (Journal of Scientific Exploration, 2025)
Suppression of truth, trauma, and toxins is widespread in the modern world. Allopathic medicine approaches disease by suppressing symptoms; individuals suppress introspection and human emotions; institutions and associated press suppress alternative views through the control of information. Social Miasm Theory, an original meta-perspective, inspired by the principles of homeopathy, identifies these suppressions as the source of miasms, chronic illnesses operating on individual and societal levels. Unless these ailments are addressed at the root, this may lead to an ever-worsening compromise of individual, societal, and global health. The solution requires a holistic approach, addressing axiomatic foundations so that researchers and reformers may perceive with fresh, unbiased eyes.